2008
DOI: 10.1002/sia.2796
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chromium and nitrogen co‐implantation on the characteristics of the passive layer developed on austenitic and duplex stainless steels

Abstract: AISI 304L and SAF 2205 stainless steel samples were implanted with chromium plus nitrogen at saturation dose in order to improve their hardness and wear properties. Consequently, the passive layer is modified so that besides the detected presence of CrN, a clear decrease in the amount of Fe oxides forming the passive layer is detected in both steels; this effect is especially important in AISI 304L. Co-implantation also causes Ni 0 enrichment present at the metal/oxide of unimplanted steels to disappear. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Recent articles also present the investigation of austenitic stainless steel and duplex stainless steels low temperature oxidation [11,12]. These previous studies conclude that the oxide films formed at low temperature and oxygen pressure consist of mixed Fe-Cr oxides, and are duplex in nature, with an outer Fe-rich spinel covering an inner rhombohedral Cr 2 O 3 layer [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent articles also present the investigation of austenitic stainless steel and duplex stainless steels low temperature oxidation [11,12]. These previous studies conclude that the oxide films formed at low temperature and oxygen pressure consist of mixed Fe-Cr oxides, and are duplex in nature, with an outer Fe-rich spinel covering an inner rhombohedral Cr 2 O 3 layer [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 94%
“…Surface analytical studies related to this processes on stainless steels have been conducted predominantly ex situ or of the initial oxidation of FeCr and FeCrNi single crystals [7,8] and simple polycrystalline alloys [9,10]. Recent articles also present the investigation of austenitic stainless steel and duplex stainless steels low temperature oxidation [11,12]. These previous studies conclude that the oxide films formed at low temperature and oxygen pressure consist of mixed Fe-Cr oxides, and are duplex in nature, with an outer Fe-rich spinel covering an inner rhombohedral Cr 2 O 3 layer [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 98%
“…The corrosion resistance of stainless steel is caused by Cr oxide (Cr 2 O 3 ) at the surface, which is considered to act as a protective layer against corrosion because of its low diffusion constants for oxygen and metal ions. Abreu et al [12,13] point out the stabilizing effect of Mo on the surface of the passive film, enhancing the formation of a layer on DSS 2205 with a higher Cr/Fe ratio. Molybdenum increases the stability of the passive film and, therefore, the ability of the stainless steel to resist localized corrosion, including pitting and crevice corrosion, particularly in environments containing chloride ions.…”
Section: Introductionmentioning
confidence: 98%
“…Recent publications have also presented investigations of the low-temperature oxidation of austenitic stainless steel and duplex stainless steels. [11,12] These studies concluded that the oxide films, formed at low temperature and at low oxygen pressure, consist of mixed Fe-Cr oxides, and are duplex in nature, with an outer, Fe-rich spinel covering an inner, rhombohedral Cr 2 O 3 layer. [13,14] This study is one of a group of studies aiming to investigate the initial phases of the oxide growth on duplex stainless steel.…”
Section: Introductionmentioning
confidence: 98%